Induction of human hepatocellular carcinoma HepG2 cell apoptosis by naringin - Banjerdpongchai R. (2017)
Naringin, a bioflavonoid found in Citrus seeds, inhibits proliferation of cancer cells. The objectives of this study were to investigate the mode and mechanism(s) of hepatocellular carcinoma HepG2 cell death induced by naringin. The cytotoxicity of naringin towards HepG2 cells proved dose-dependent, measured by MTT assay. Naringin-treated HepG2 cells underwent apoptosis also in a concentration related manner, determined by annexin V-fluorescein isothiocyanate (FITC) and propidium iodide (PI) employing flow cytometry. Mitochondrial transmembrane potential (MTP) measured using 3,3'-dihexyloxacarbocyanine iodide (DiOC 6 ) and flow cytometer was reduced concentration-dependently, which indicated influence on the mitochondrial signaling pathway. Caspase-3, -8 and -9 activities were enhanced as evidenced by colorimetric detection of para-nitroaniline tagged with a substrate for each caspase. Thus, the extrinsic and intrinsic pathways were linked in human naringin-treated HepG2 cell apoptosis. The expression levels of pro-apoptotic Bax and Bak proteins were increased whereas that of the anti-apoptotic Bcl-xL protein was decreased, confirming the involvement of the mitochondrial pathway by immunoblotting. There was an increased expression of truncated Bid (tBid), which indicated caspase-8 proteolysis activity in Bid cleavage as its substrate in the extrinsic pathway. In conclusion, naringin induces human hepatocellular carcinoma HepG2 cell apoptosis via mitochondria-mediated activation of caspase-9 and caspase-8-mediated proteolysis of Bid. Naringin anticancer activity warrants further investigation for application in medical treatment.